Generative and Transformational Techniques in Software Engineering II International Summer School, GTTSE 2007, Braga, Portugal, July 2-7. 2007, Revised Papers - Lämmel, Ralf.; Visser, Joost; Saraiva, João.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This tutorial book presents an augmented selection of the material presented at the International Summer School on Generative and Transformational Techniques in Software Engineering, GTTSE 2007, held in Braga, Portugal, in July 2007. The 7 tutorial lectures presented together with 5 short tutorials and 4 contributions to the participants workshop were carefully selected during multiple rounds of reviewing and improvement. The tutorials given by renowned representatives of complementary approaches and problem domains combine foundations, methods, examples, and tool support.
Full Tutorials -- Design Space of Heterogeneous Synchronization -- Software Reuse beyond Components with XVCL (Tutorial) -- .QL: Object-Oriented Queries Made Easy -- Transforming Data by Calculation -- How to Write Fast Numerical Code: A Small Introduction -- A Gentle Introduction to Multi-stage Programming, Part II -- WebDSL: A Case Study in Domain-Specific Language Engineering -- Short Tutorials -- Model-Driven Engineering of Rules for Web Services -- An Introduction to Context-Oriented Programming with ContextS -- A Landscape of Bidirectional Model Transformations -- Evolving a DSL Implementation -- Adding Dimension Analysis to Java as a Composable Language Extension -- Participants Contributions -- Model Transformations for the Compilation of Multi-processor Systems-on-Chip -- Implementation of a Finite State Machine with Active Libraries in C++ -- Automated Merging of Feature Models Using Graph Transformations -- Modelling the Operational Semantics of Domain-Specific Modelling Languages.
Keywords: Software engineering; Computer programming; Computer communication systems; Computers; Microprogramming .; Software Engineering/Programming and Operating Systems; Programming Techniques; Computer Communication Networks; Software Engineering; Computation by Abstract Devices; Control Structures and Microprogramming